The Influence of Organizational Culture and Leadership Style Through the Work Environment on the Performance of Employees of the Badung Regency Health Service - Natarimbawa, I Wayan; Karta, Ni Luh Putu Agustini; Irwanti, Ni Ketut Dewi (PT Mattawang Mediatama Solution, 2025)
The objective of this study is to examine the influence of organizational culture and leadership style on the work environment, with a particular emphasis on employee performance. The population under study comprised all employees at the Badung Regency Health Office, with a total of 73 individuals. The sampling technique that was implemented was the census method, also referred to as the saturated sample technique. This method involves the inclusion of the entire population as the research sample. The data analysis technique employed a comprehensive approach, incorporating validity and reliability tests, classical assumption tests, and path analysis to investigate the relationships among the variables more thoroughly. The findings of the analysis suggested that both organizational culture and leadership style exerted a positive and significant influence on the work environment. Moreover, the findings indicated a positive and significant relationship between organizational culture, leadership style, and work environment with employee performance. Furthermore, the work environment was identified as an intervening variable in the relationship between organizational culture and employee performance, as well as in the relationship between leadership style and employee performance at the Badung Regency Health Office. In light of these findings, the study posits that the Head of the Badung Regency Health Office should endeavor to enhance organizational culture by improving employee performance and personal character. Consequently, leadership style should be enhanced by fortifying the capacity to motivate employees and the ability to regulate emotions. Furthermore, endeavors to enhance the work environment should be implemented through the cultivation of more positive relationships between supervisors and subordinates, the establishment of a conducive and supportive working atmosphere, and the maintenance of harmonious relations among colleagues. It is anticipated that these initiatives will enhance employee performance by facilitating enhanced collaboration and more effective utilization of working time.